Handbook of mango fruit production, postharvest science, processing technology and nutrition Muhammad Siddiq, Jeffrey K. Brecht, Jiwan S. Sidhu. - Sidhu, Jiwan S.; Brecht, Jeffrey K. 1942-; Siddiq, Muhammad 1957- (John Wiley & Sons, Ltd., 2017)
"Mango is the most widely consumed tropical fruit in the world after bananas. Global production of the mango has more than doubled in the last three decades, to around 35 million metric tons (Source: UNCTAD: United Nations Conference on Trade and Development). The mango market has grown considerably over the same time period, with the two major import markets being the United States and European Union countries. In the US, per capita mango consumption increased from 0.26 pounds/year in 1980 to 2.10 pounds/year in 2010 (source: USDA-ERS). With the increased consumption of this nutrient-rich fruit, the processed mango market has seen a similar growth, especially in fresh-cut fruit, juice and beverages, and dried products. Given such a tremendous significance of mango fruit and its processed products in the world commerce, a new book on mango technology, production, postharvest science, processing and nutrition is appropriate and timely. The work will be unique in the sense that no other book currently available in the market covers the breadth and depth of topics suggested in this proposal. It will provide contemporary information that brings together current knowledge and practices in the value-chain of mango fruit from production through consumption. The book will be unique in the sense that it will include coverage of production and postharvest technologies, innovative processing technologies, packaging, and quality management. This value-chain approach to the topic coverage is a unique feature of this book. In the last 10 years or so, health-beneficial bioactive compounds, especially antioxidants, have emerged an important area of research; however, there are no books that cover this important aspect in mangoes"